Non‐clinical interventions for reducing unnecessary caesarean section - Chen, Innie (2019)
Background: Caesarean section rates are increasing globally. The factors contributing to this increase are complex, and identifying interventions to address them is challenging. Non‐clinical interventions are applied independently of a clinical encounter between a health provider and a patient. Such interventions may target women, health professionals or organisations. They address the determinants of caesarean births and could have a role in reducing unnecessary caesarean sections. This review was first published in 2011. This review update will inform a new WHO guideline, and the scope of the update was informed by WHO’s Guideline Development Group for this guideline. Objectives: To evaluate the effectiveness and safety of non‐clinical interventions intended to reduce unnecessary caesarean section. Search methods: We searched CENTRAL, MEDLINE, Embase, CINAHL and two trials registers in March 2018. We also searched websites of relevant organisations and reference lists of related reviews. Selection criteria: Randomised trials, non‐randomised trials, controlled before‐after studies, interrupted time series studies and repeated measures studies were eligible for inclusion. The primary outcome measures were: caesarean section, spontaneous vaginal birth and instrumental birth. Data collection and analysis: We followed standard methodological procedures recommended by Cochrane. We narratively described results of individual studies (drawing summarised evidence from single studies assessing distinct interventions). Main results: We included 29 studies in this review (19 randomised trials, 1 controlled before‐after study and 9 interrupted time series studies). Most of the studies (20 studies) were conducted in high‐income countries and none took place in low‐income countries. The studies enrolled a mixed population of pregnant women, including nulliparous women, multiparous women, women with a fear of childbirth, women with high levels of anxiety and women having undergone a previous caesarean section. Overall, we found low‐, moderate‐ or high‐certainty evidence that the following interventions have a beneficial effect on at least one primary outcome measure and no moderate‐ or high‐certainty evidence of adverse effects. Interventions targeted at women or families. Childbirth training workshops for mothers alone may reduce caesarean section (risk ratio (RR) 0.55, 95% confidence interval (CI) 0.33 to 0.89) and may increase spontaneous vaginal birth (RR 2.25, 95% CI 1.16 to 4.36). Childbirth training workshops for couples may reduce caesarean section (RR 0.59, 95% CI 0.37 to 0.94) and may increase spontaneous vaginal birth (RR 2.13, 95% CI 1.09 to 4.16). We judged this one study with 60 participants to have low‐certainty evidence for the outcomes above. Nurse‐led applied relaxation training programmes (RR 0.22, 95% CI 0.11 to 0.43; 104 participants, low‐certainty evidence) and psychosocial couple‐based prevention programmes (RR 0.53, 95% CI 0.32 to 0.90; 147 participants, low‐certainty evidence) may reduce caesarean section. Psychoeducation may increase spontaneous vaginal birth (RR 1.33, 95% CI 1.11 to 1.61; 371 participants, low‐certainty evidence). The control group received routine maternity care in all studies. There were insufficient data on the effect of the four interventions on maternal and neonatal mortality or morbidity. Interventions targeted at healthcare professionals Implementation of clinical practice guidelines combined with mandatory second opinion for caesarean section indication slightly reduces the risk of overall caesarean section (mean difference in rate change ‐1.9%, 95% CI ‐3.8 to ‐0.1; 149,223 participants). Implementation of clinical practice guidelines combined with audit and feedback also slightly reduces the risk of caesarean section (risk difference (RD) ‐1.8%, 95% CI ‐3.8 to ‐0.2; 105,351 participants). Physician education by local opinion leader (obstetrician‐gynaecologist) reduced the risk of elective caesarean section to 53.7% from 66.8% (opinion leader education: 53.7%, 95% CI 46.5 to 61.0%; control: 66.8%, 95% CI 61.7 to 72.0%; 2496 participants). Healthcare professionals in the control groups received routine care in the studies. There was little or no difference in maternal and neonatal mortality or morbidity between study groups. We judged the certainty of evidence to be high. Interventions targeted at healthcare organisations or facilities Collaborative midwifery‐labourist care (in which the obstetrician provides in‐house labour and delivery coverage, 24 hours a day, without competing clinical duties), versus a private practice model of care, may reduce the primary caesarean section rate. In one interrupted time series study, the caesarean section rate decreased by 7% in the year after the intervention, and by 1.7% per year thereafter (1722 participants); the vaginal birth rate after caesarean section increased from 13.3% before to 22.4% after the intervention (684 participants). Maternal and neonatal mortality were not reported. We judged the certainty of evidence to be low. We studied the following interventions, and they either made little or no difference to caesarean section rates or had uncertain effects. Moderate‐certainty evidence suggests little or no difference in caesarean section rates between usual care and: antenatal education programmes for physiologic childbirth; antenatal education on natural childbirth preparation with training in breathing and relaxation techniques; computer‐based decision aids; individualised prenatal education and support programmes (versus written information in pamphlet). Low‐certainty evidence suggests little or no difference in caesarean section rates between usual care and: psychoeducation; pelvic floor muscle training exercises with telephone follow‐up (versus pelvic floor muscle training without telephone follow‐up); intensive group therapy (cognitive behavioural therapy and childbirth psychotherapy); education of public health nurses on childbirth classes; role play (versus standard education using lectures); interactive decision aids (versus educational brochures); labourist model of obstetric care (versus traditional model of obstetric care). We are very uncertain as to the effect of other interventions identified on caesarean section rates as the certainty of the evidence is very low. Authors' conclusions: We evaluated a wide range of non‐clinical interventions to reduce unnecessary caesarean section, mostly in high‐income settings. Few interventions with moderate‐ or high‐certainty evidence, mainly targeting healthcare professionals (implementation of guidelines combined with mandatory second opinion, implementation of guidelines combined with audit and feedback, physician education by local opinion leader) have been shown to safely reduce caesarean section rates. There are uncertainties in existing evidence related to very‐low or low‐certainty evidence, applicability of interventions and lack of studies, particularly around interventions targeted at women or families and healthcare organisations or facilities.